Evidence‐based (S3) Guideline on (anogenital) Lichen sclerosus. (22nd July 2015) - Kirtschig, G.; Becker, K.; Günthert, A.; Jasaitiene, D.; Cooper, S.; Chi, C.‐C.; Kreuter, A.; Rall, K.K.; Aberer, W.; Riechardt, S.; Casabona, F.; Powell, J.; et al.
Abstract Lichen sclerosus (LS) is an inflammatory skin disease that usually involves the anogenital area. All patients with symptoms or signs suspicious of lichen sclerosus should be seen at least once initially by a physician with a special interest in the disease in order to avoid delay in diagnosis, as early treatment may cure the disease in some and reduce or prevent scarring. The diagnosis is made clinically in most cases. Biopsies should only be performed under certain circumstances. The gold standard for treatment remains potent to very potent topical steroids; however, mild and moderate disease in boys and men may be cured by circumcision. Certain triggers should be avoided. http://www.euroderm.org/images/stories/guidelines/2014/S3-Guideline-on-Lichen-sclerosus.pdf<ext-link ext-link-type="uri" xlink:href="http://www.awmf.org/fachgesellschaften/mitgliedsgesellschaften/visitenkarte/fg/deutsche-gesellschaft-fuer-gynaekologie-und-geburtshilfe-dggg.html" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">http://www.awmf.org/fachgesellschaften/mitgliedsgesellschaften/visitenkarte/fg/deutsche-gesellschaft-fuer-gynaekologie-und-geburtshilfe-dggg.html.